The Effect of Giving Ambon Banana to Increasing Haemoglobin Levels in Takengon Adolescence in the Junior High School 42 in 2022 - Kismiasih Adethia; Sukarni (Science Midwifery, 2022)
The incidence of anemia in Indonesia is still quite high. Based on data from Riskesdas 2018, the prevalence of anemia in adolescents is 32%, meaning that 3-4 out of 10 adolescents suffer from anemia. This is influenced by the habit of nutritional intake that is not optimal and lack of physical activity. Ambon bananas are enriched with iron which is effective for controlling iron deficiency and almost entirely can be absorbed by the body. Ambon bananas also contain vitamin C which can help increase iron absorption. Vitamin C increases absorption because it reduces iron in the form of ferric to ferrous. Vitamin C increases the absorption of iron from food through the formation of ferrous ascorbate complexes. The combination of 200 mg of ascorbic acid with iron salts can increase iron absorption by 25% - 50% (Fenni, 2018).) The purpose of this study was to analyze the effect of giving Ambon bananas to increase hemoglobin levels in adolescents at SMP 42 Takengon in 2022. Types of research used in this research is quantitative research with Quasy Experiment research design with Two Group with pre test post test design which consists of 2 groups, control group and experimental group. This research was conducted at SMP 42 Takengon A total of 68 people with a total sample of 26 people who have anemia. The sampling technique used is purposive sampling. Bivariate analysis using Mann Whitney statistical test. This study obtained the results of P-Value 0.037 (P <0.05) it can be concluded that Ha is accepted, namely the effect of giving Ambon bananas to the increase in hemoglobin in adolescents